Modeling and Contact Analysis of Internal Meshing Nutation Spiral Bevel Gear with Different Tooth Profiles based on General Tooth Surface Model - Zheng Lin; Ligang Yao (Jixie chuandong)
The derivation process of the tooth surface mathematical model of the internal meshing spiral bevel gears for nutation drive is complex. In order to establish different tooth profiles of the spiral bevel gears and carry out load contact analysis， the general tooth surface mathematical model of the crown gear is established by using the general normal basic tooth profile. According to the meshing relationship between the crown gear and the external and internal spiral bevel gears， the general tooth surface mathematical model of the nutation spiral bevel gear is derived. Then the tooth surface models and three-dimensional models of the nutation spiral bevel gears with involute and double circular-arc as the normal basic tooth profiles are established. The load contact analysis of spiral bevel gears with high and low power and different tooth profiles is carried out by using the finite element software. The results show that the load has a great influence on the load contact characteristics of involute spiral bevel gear. The double circular-arc spiral bevel gear have the advantages of larger load capacity and more stable transmission compared with spiral bevel gear.